Inhibition of poly (ADP-ribose) polymerase 1 in neuron cells might enhance the therapeutic effect of leonurine under cholesterol stimulation - Bo Hou; Zhigang Huan; Chao Zhang; Zhiyong Chen; Lingmei Ha; Shengxuan Huang (Folia Neuropathologica, 2022)
Atherosclerosis (AS) is a chronic inflammatory disease with high morbidity and mortality worldwide and is the pathologic basis of cerebral-cardiovascular disease. Cerebral infarction is caused by cerebral ischemia in the deep brain stem or cerebral hemisphere, and small vessel atherosclerosis is the pathophysiological basis of lacunar cerebral infarction. In this study, we found that inhibition of PARP1 in neuronal cells increased the proliferation rate of cells, reduced the concentration of cholesterol in neuronal cells, inhibited the expression and secretion of proinflammatory factors and promoted the expression and secretion of proangiogenic factors. In addition, the reverse transport process of cholesterol and autophagy process were activated in neuron cells by detecting the target proteins using western blotting analysis, and further experiments found that this process might be mediated by activation of the PI3K/AKT/mTOR signalling pathway. Thus, we thought inhibition of PARP1 might be a new therapeutic method for cerebral-cardiovascular disease.